Investigating the hydrogen storage capacity of surfactant modified graphene. (February 2019) - Xu, Tao; Chen, Jiayu; Yuan, Wenhui; Li, Li; Sun, Yongjun; Wu, Huijun; Yang, Lixiu
Abstract: As the depletion of traditional fossil fuels and environmental pollution become a serious problem of human society, researchers are actively finding renewable green energy sources. Considered as a clean, efficient and renewable alternative, Hydrogen energy is considered the most promising energy source. However, the safe and efficient storage of hydrogen has become the major problem that hinders its application. To solve this gap, this paper proposes to utilize surfactant modified graphene for hydrogen storage. With Hummers method and ultrasonic stripping method, this study prepared graphene from graphene oxide with NaBH4. Surfactant sodium dodecylbenzene sulfonate (SDBS) was used as a dispersant during the reduction process to produce the dispersion-stabilized graphene suspensions. The characteristics of the graphene suspensions then were examined by XRD, SEM, TEM, FT-IR, Raman, XPS, TG, and N2 adsorption-desorption tests. The hydrogen adsorption properties of the samples were investigated with Langmuir and Freundlich fitting. The results show that the adsorption behavior is consistent with the Freundlich adsorption model and the process is a physical adsorption.